(3eSGdc GdCagGe aj TQM TQGFY GdESdGes - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s ((3MSf Hf gGTe Hf cQe Gddgs)
(3ChdgG (B:s
(3GdbSe GdKGdK aj GdEjbGYGJ hgj CMO YTQ cJGHG , bhdg cJGH GdWdGb ; GdWdGb dZI Md bjO hjWdb Ydi GdEQSGd hGdJQc , jGbddG fGbI WGdb Gj eQSdI JOYi MjK JTGA hWdbJ Gdbhe EPG JQcJge (B...s
(3BNQgG (B:s
... (3Ke JLeY GdMHGJ HYVgG Edi HYVgG Jcf SJI hYTQjf MHI hGdCQRGJ KdGKI YTQ CQRI hCLRGDgG JSYI hKdGKjf LRAG ef KdGKI YTQ LRAG ef CQRI hPdc KdGK CQRGJ (B... (3aJHjf Cf GdbSeI UMjMI hGddg Gdehabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B20/3516s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis